Prognostic factors associated with non-remission and low disease activity status af ter one year of psoriatic arthritis patients treatment in real practice - E. Yu. Loginova; T. V. Korotaeva; E. E. Gubar; Yu. L. Korsakova; S. I. Glukhova; E. L. Nasonov (Научно-практическая ревматология, 2023)
Background. Remission/low disease activity (LDA) are acceptable goal of psoriatic arthritis (PsA) treatment. Prognostic factors for non-remission/LDA hasn’t been fully studied yet and data is limited. The aim – to determine the prognostic factors associated with non-remission/LDA status within 1 year of treatment in PsA pts in real practice. Methods. 292 pts (M/F=122/170) with active PsA fulfilling the CASPAR criteria were included. Mean age 46.1±12.5 years (yrs), PsA duration 10.4±7.1 months (mos), psoriasis (Ps) duration 19.32±12.08 mos, body mass index (BMI) 27.7±5.6 kg/m2 , median (Me) of DAPSA – 23.8 [14.7; 37.4]. 182 pts was given therapy with synthetic (s) DMARDs predominantly methotrexate (MTX), 110 pts – bDMARDs as monotherapy or with combination with MTX or other sDMARDs. At baseline (BL) and at 1 year of therapy PsA activity by tender/swelling joint count (TJC)/68, (SJC)/66, pain (VAS), Patient global assessment disease activity (PtGA, VAS), CRP (mg/l), dactylitis, enthesitis by LEI and plantar fascia, BSA (%), HAQ, DAPSA were evaluated. DAPSA>28 indicate high disease activity (HDA), DAPSA=15–28 – moderate activity (MoDA), DAPSA=5–14 – LDA, DAPSA≤4 – remission. By 1 year of therapy the proportion of pts who had not reached remission or LDA were calculated. The one-factor model of logistic regression was used to identify a group of features that are associated with remission or LDA  nonachievement. M±SD, Me [Q25; Q75], Min–Max, %, t-test, Peаrson χ2 , Mann – Whitney tests, ORs with 95% CI were performed. All p<0.05, were considered to indicate statistical significance. Results. At 1 year of therapy 116 pts of 292 (40%) have HDA/MoDA by DAPSA. Remission/LDA was reached in 176 (60%) pts, 110 of them (62.5%) were treated with bDMARDs. Comparative analysis in both groups and one-factor model of logistic regression showed the following features at BL were associated with non-remission/LDA status: TJC>5 (p<0.001), SJC>3 (p<0.001), CRP>10 mg/l (p<0.001), HAQ>0.5 (p<0.001), presence of enthesitis (p<0.001), dactylitis (p<0.001), BMI>30 (p<0.002) and had to be treated with sDMARDs. PsA pts with combination of these clinical features at first visit have a higher risk of not achieving remission/LDA status in comparison to PsA pts without them, OR with 95% CI. Conclusion. In real practice remission/LDA cannot achieve 40% PsA pts despite going through therapy. It is a combination of clinical fea tures at BL – TJC>3, SJC>5, CRP>10 mg/l, HAQ>0.5, presence of enthesitis, dactylitis, BMI>30 kg/m2 and sDMARDs monotherapy – that constitutesa prognostic factor with negative impact on achievement remission/LDA after 1 year of treatment.